LEADERSHIP POLICY URGENCY: DEVELOPING THE SANTRI CULTURE IN ISLAMIC BOARDING SCHOOLS: URGNSI KEBIJAKAN PIMPINAN: MENGEMBANGKAN BUDAYA SANTRI DI PONDOK PESANTREN - M. Armando Farshal Mz; Fadlilah Fadlilah; Fransisko Chaniago; Sizka Farwati (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the urgency of leadership policies in developing the santri culture at Pondok Pesantren PKP Al-Hidayah, Kecamatan Kota Baru, Jambi Province. Specifically, the study examines the forms of santri culture and the strategic role of leadership policies in its development. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation with informants including the pesantren leadership, supervisors, dormitory caretakers, Orsada administrators in charge of security and teaching, as well as the santri. The findings indicate that the development of santri culture is systematically carried out through the strengthening of disciplinary, participatory, and academic cultures integrated across all santri activities. Queuing habits, active involvement in pesantren activities, and academic and foreign language practices have been proven to shape santri character to be disciplined, responsible, independent, and socially prepared. Leadership policies play a strategic role in maintaining order, enforcing discipline, and ensuring the achievement of the pesantren’s vision and mission. Additionally, curriculum adaptation, foreign language proficiency, and technological utilization demonstrate the pesantren’s readiness to respond to global challenges, positioning it as an institution for character building and the sustainable development of santri competencies